Global occupational health - Guidotti, Tee L. (New York ; Oxford : Oxford University Press, 2011)
'Global Occupational Health' is a comprehensive introductory textbook designed for the preparation of professionals in occupational health. The textbook is intended for use in basic to mid-level courses, providing the reader or student with a solid foundation from which to pursue more specialized studies.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Industrial hygiene; World health